Understanding Figure of Sunan Kudus as the Internalization of Gusjigang to Develop Entrepreneurship in the Global Competition - Rabith Jihan Amaruli (Diponegoro University, 2017)
This article discusses the Gusjigang, cultural values of Kudus people through the understanding figure of Sunan Kudus, the founder of the city. The acronym of Gusjigang is derived from Javanese language, Gus-Ji-Gang, means Bagus (good, capable, or something related to goodness), Ngaji (learning the Qur’an or learn about anything in life), and Dagang (commerce, trade, or everything related to the spirit of business and entrepreneurship). Based on the oral tradition of Kudus people, “already” believed that Gusjigang could not be separated from the figure of Sunan Kudus and the history of the city.